2021
DOI: 10.3389/fcvm.2021.740839
|View full text |Cite
|
Sign up to set email alerts
|

Catecholamine Surges Cause Cardiomyocyte Necroptosis via a RIPK1–RIPK3-Dependent Pathway in Mice

Abstract: Background: Catecholamine surges and resultant excessive β-adrenergic stimulation occur in a broad spectrum of diseases. Excessive β-adrenergic stimulation causes cardiomyocyte necrosis, but the underlying mechanism remains obscure. Necroptosis, a major form of regulated necrosis mediated by RIPK3-centered pathways, is implicated in heart failure; however, it remains unknown whether excessive β-adrenergic stimulation-induced cardiac injury involves necroptosis. Hence, we conducted the present study to address … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 70 publications
0
10
0
Order By: Relevance
“…The pathological increase in the concentration of circulating catecholamines and their excessive release from the cardiac sympathetic nerve endings lead to direct damage to the cardiomyocytes [30]. The pathophysiological mechanisms involved in catecholamineinduced myocardial injury include increased oxygen demand of the cardiomyocytes with insufficient supply, oxidative stress, calcium overload, myofibril over-contraction, and upregulation of the expression and release of inflammatory cytokines [31][32][33][34][35][36][37][38][39][40][41][42]. Indeed, histopathological examinations of the myocardium of rats treated with supraphysiological doses of catecholamines showed focal necrosis and degeneration of the cardiomyocytes, disordered myofibrils, advanced cytoplasmic vacuolization, myocardial infiltration with inflammatory cells, and tissue fibrosis [43][44][45].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The pathological increase in the concentration of circulating catecholamines and their excessive release from the cardiac sympathetic nerve endings lead to direct damage to the cardiomyocytes [30]. The pathophysiological mechanisms involved in catecholamineinduced myocardial injury include increased oxygen demand of the cardiomyocytes with insufficient supply, oxidative stress, calcium overload, myofibril over-contraction, and upregulation of the expression and release of inflammatory cytokines [31][32][33][34][35][36][37][38][39][40][41][42]. Indeed, histopathological examinations of the myocardium of rats treated with supraphysiological doses of catecholamines showed focal necrosis and degeneration of the cardiomyocytes, disordered myofibrils, advanced cytoplasmic vacuolization, myocardial infiltration with inflammatory cells, and tissue fibrosis [43][44][45].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, histopathological examinations of the myocardium of rats treated with supraphysiological doses of catecholamines showed focal necrosis and degeneration of the cardiomyocytes, disordered myofibrils, advanced cytoplasmic vacuolization, myocardial infiltration with inflammatory cells, and tissue fibrosis [43][44][45]. Necrosis is the major pathological feature of catecholamine-induced myocardial injury [42,46]. However, recently, Wu et al (2021) have proven that, in adult mixed-sex mice injected subcutaneously with ISO, a large proportion of cardiomyocyte necrosis induced by ISO is driven by necroptosis and is mediated by the RIPK1-RIPK3-MLKL pathway.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The peri-infarct period is characterized by elevated levels of endogenous catecholamines(46) that activate ARs on cardiomyocytes. High concentrations of the -AR agonist isoproterenol (85 mg/kg s.c.) induce cardiomyocyte necrosis with induction of RIP1 and RIP3 in mice (47), suggesting that -AR hyperactivation may promote necroptosis to contribute to the pathobiology of MI. Regulation of necroptosis by 1-ARs has not been studied previously.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, further investigation into the role of mTORC1 signaling in ISO‐induced myocardial injury and deciphering whether mTORC1‐regulated macroautophagy is potentially involved are warranted. Additionally, our previous study showed that a large proportion of cardiomyocyte necrosis induced by high doses of ISO was necroptosis mediated by the RIPK1–RIPK3–MLKL pathway (Wu et al., 2021 ). The effect of mTORC1 in the induction of cardiomyocyte necroptosis by ISO remains unexamined although some reports suggested a potential association between mTORC1 and RIPK1–‐RIPK3–MLKL necroptotic pathway induced by other etiologies (Abe et al., 2019 ; Liu et al., 2014 ; Ogasawara et al., 2017 ; Xie et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%